Penentuan Daerah Luahan (Discharge Area) di Utara Sesar Baribis Wilayah Kabupaten Subang Provinsi Jawa Barat - Tifana Amalya; Yunus Ashari; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2022)
Abstract. The use of clean water to meet human needs is increasing along with the rise of population and technological developments. The fulfillment of the needs of clean water can be obtained from surface water or groundwater. Areas that utilize groundwater with a fairly large number are industrial areas such as Subang regency which is defined as the area of the potential industry according to the Ministry of Industry. The industrial area is located in the Northern part of the Fault Baribis Subang suspected of being in the recharge zone of the Subang groundwater basin. Therefore the groundwater conservation efforts are needed with the determination of the discharge areas to regulate the industrial zone so they did not take on the land recharge function. This research is intended to identify the emergence of the Spring and the quality of groundwater (Total Dissolved Solid and Electrical conductivity) as well as the Groundwater level in the determination of aquifer systems and the delineation of discharges zone. The springs are scattered with the discharge 0.1 – 18 l/sec are found in the form of a lake that still retain water during the long dry season. The emergence of the springs is controlled by the activity of the baribis fault and the presence of a layer of groundwater level is truncated by topography and the porous rocks that overlap the impermeable rocks layer. Based on the flownet dug wells and boreholes obtained the groundwater flow direction leads from the Ciater groundwater basin to Subang groundwater basin pass Non-groundwater basin (South to North). Based on the research it can be concluded that the Northern part of the Baribis Fault has 2 (two) system aquifer, which is an unconfined aquifer located in the Southern part with evidenced by the head of the groundwater level dug wells and bore wells are relatively the same and the confined aquifer in the industrial areas is evidenced by the head of the groundwater level wells being relatively higher. So the area of discharges can be described based on the information of the confined aquifer and the emergence of the springs in the study area. Abstrak. Pemanfaatan air bersih untuk memenuhi kebutuhan manusia semakin meningkat dengan bertambahnya populasi penduduk dan perkembangan teknologi. Pemenuhan kebutuhan air bersih dapat diperoleh dari air permukaan maupun airtanah. Daerah yang memanfaatkan airtanah dengan jumlah yang cukup besar adalah kawasan industri seperti Kabupaten Subang yang ditetapkan sebagai daerah potensi industri menurut Kementerian Perindustrian. Kawasan industri tersebut berlokasi di bagian Utara Sesar Baribis Kabupaten Subang yang diduga berada pada zona resapan CAT Subang. Maka dari itu, diperlukan upaya konservasi airtanah dengan penentuan zona luahan (discharge area) untuk menertibkan kawasan industri agar tidak mengambil fungsi lahan pada zona resapan (recharge area). Penelitian ini bertujuan untuk mengidentifikasi kemunculan mata air dan kualitas airtanah (Total Dissolved Solid dan Daya Hantar Listrik) serta Muka Airtanah (MAT) dalam penentuan sistem akuifer dan deliniasi zona luahan. Mata air tersebar dengan debit 0,1 – 18 l/detik yang ditemukan dalam bentuk situ/danau yang masih menyimpan air saat musim kemarau panjang. Kemunculan mata air dikontrol oleh aktivitas sesar baribis dan adanya lapisan MAT yang terpotong topografi serta batuan porous yang menindih lapisan impermeable. Berdasarkan flownet sumur gali dan sumur bor diperoleh arah aliran airtanah mengarah dari CAT Ciater ke CAT Subang melewati Non CAT (Selatan ke Utara). Berdasarkan penelitian dapat disimpulkan bahwa bagian Utara Sesar Baribis berada pada 2 (dua) sistem akuifer yaitu akuifer tidak tertekan yang berada di bagian Selatan dibuktikan dengan head MAT sumur gali dan sumur bor yang relative sama dan akuifer tertekan di beberapa kawasan industri dibuktikan dengan head MAT sumur bor yang relative lebih tinggi. Sehingga daerah luahan dapat digambarkan berdasarkan informasi akuifer tertekan dan kemunculan mata air di daerah penelitian.